Ernst Behler's "The Contemporary and the Posthumous": Roundtable Discussion - Adams, Hazard; Behler, Ernst; Birus, Hendrick; Derrida, Jacques; Iser, Wolfgang; Krieger, Murray; Miller, Hillis; Pfeiffer, Ludwig; Readings, Bill; Wang, Ching-hsien; Yu, Pauline (Surfaces)

(untitled) (Les Presses de l’Université de Montréal, 1996)
This roundtable discussion of "The Contemporary and the Posthumous", Ernst Behler's contribution to the first International Conference for Humanistic Discourses, was held in April, 1994. The papers of this first meeting of the ICHD have been published in volume 4 of Surfaces (1994).